Teaching NeuroImage: Isolated Unilateral Hypoglossal Nerve Palsy due to Skull Base Meningioma. (19th October 2021) - Coenen, Jessica; Cleaver, Jonathan; James, Richard; Chohan, Gurjit
Abstract : A 73-year-old woman presented with a 6-month history of intermittent lisp, drooling, and aspiration. Initial assessment showed right hemitongue atrophy (Figure 1) with ipsilateral fasciculations and weakness. Residual neurologic examination was unremarkable. MRI brain confirmed a right hypoglossal nerve palsy (HNP) secondary to a hypoglossal canal meningioma, with classical radiologic appearances (Figure 2).